A Postcolonial reading of a selection of short stories by W. Somerset Maugham - Sisti, Esteban Roberto (2021)
Fil: Sisti, Esteban Roberto. Universidad Nacional del Litoral. Facultad de Humanidades y Ciencias; Argentina.